A cross sectional study on out born neonate referral pattern and factors influencing the neonatal outcomes among the out born neonates admitted to sick newborn care units of a government teaching hospital - Khot, Poornima Basavraj; H. L., Thejeshwari; ., Kumar; Sundar, M.; Kumar, Prasanna (International Journal Of Community Medicine And Public Health, 2020)
Background: Neonatal mortality rate (NMR) is one of the major contributors to infant mortality rate. The neonatal mortality depends on many factors birth weight, gestational age, post-natal care; it also depends on maternal social and environmental conditions which contribute to the social determinants of maternal health. This study was taken up to identify maternal social determinants contributing to outcome among outborn neonates in order to reduce neonatal deaths. The present was conducted to assess the outcome among the outborn neonates and assess the maternal social determinants of health affecting the outcome. Methods: A cross sectional study conducted in sick newborn care units (SNCU), Hassan Institute of Medical Sciences, Hassan among all out born neonates. After taking prior written consent, all mothers/bystanders of outborn neonates were interviewed using predesigned, pretested semi-structured proforma. Social factors, environmental conditions and antenatal care affecting the maternal health were collected. Neonatal outcome data was collected from SNCU register. The mothers/bystanders of outborn neonates not willing to give consent and re-admitted neonates were excluded from the study. Data analysis was done using SPSS V20.0. Results: Of 353 outborn neonates admitted, 16.1% was mortality rate. Number of antenatal care visits, consumption of iron tablets, gestational age, high risk mother, staff attending delivery, birth weight, referral time (at p≤0.5) and distance from hospital, passive smoking exposure, maternal services utilization (at p-value <0.1) were significantly associated with poor outcome among outborn neonates. Conclusions: There is need for establishment of SNCUs at sub-divisional levels.